THE USE OF ANAGRAMS TO INCREASE STUDENTS’ ENGLISH VOCABULARY MASTERY - Yugi Diraga Prawiyata (JURNAL PENELITIAN PENDIDIKAN BAHASA DAN SASTRA, 2020)
The objective of the research was to find out whether Anagrams increased students’ vocabulary mastery and to find out how was the students’ mastery in learning vocabulary by using Anagrams. The subject of this research was the second year students of MTs Al Washliyah 32 Sei Bamban in academic year 2018/2019 which consisted of thirty people. In this research, it was applied the Classroom Action Research (CAR). Technique of collecting the data was to use a written test, in a certain topic applied in Anagram technique where the researcher made the indicators as the test consisted of twenty where each number amounts to 5. Then the researcher observed the students’ action while the use of Anagram technique was implemented and also the students’ opinion about the effectiveness of Anagram technique toward their vocabulary mastery. The result of the research showed that the students’ score in the second cycle was higher (85-95) than the first cycle (68-90). In other words it indicated that the use of Anagrams really increase students’ vocabulary mastery.